Pengaruh Model Pembelajaran ARIAS (Assurace, Relevance, Interest, Assessment, Satisfaction) Terhadap Kemampuan Menulis Teks Ulasan Cerpen Siswa Kelas XI SMK Negeri 1 Lubuk Pakam Tahun Ajar 2022/2023 - Ismi Chairani Sartika Husnul; Khairil Ansari (Medan Resource Center, 2023)
This study examined the impact of the ARIAS learning model (Assurance, Relevance, Interest, Assessment, Satisfaction) on the writing ability of short story reviews among class XI students at SMK Negeri 1 Lubuk Pakam. Using Cluster Random Sampling, 72 students were selected for the control and experimental classes. The experimental method with a Posttest-Only Control Design was employed, and a posttest served as the data collection instrument. The results showed that the experimental class (mean = 85.94, SD = 5.89) outperformed the control class (mean = 57.33, SD = 8.38). Preceding hypothesis testing, normality and homogeneity tests confirmed the suitability of the data. The t-test indicated a significant difference (t = 16.702, df = 70, p < 0.05), rejecting the null hypothesis and accepting the alternative hypothesis. Consequently, the ARIAS learning model positively influenced the writing proficiency of class XI students at SMK Negeri 1 Lubuk Pakam.